Can non-timber forest products match tropical forest conservation and development objectives? - Arnold, J.E.M.; Ruíz Pérez, M. (2001)
The contributions that non-timber forest products (NTFPs) can make to rural livelihoods, and the fact that their use is less ecologically destructive than timber harvesting, have encouraged the belief that more intensive management of forests for such products could contribute to both development and conservation objectives, and have led to initiatives to expand commercial use of NTFPs. This paper reviews evidence that indicates that this conservation through commercialization thesis needs to be revised. In practice, the selective nature of market demand, and the uneven distribution of resources of use value within forests, mean that with NTFP harvesting the resource can become altered and degraded. The pressures that market forces can place on local control mechanisms, and the conflicting interests of those using forest resources for subsistence and income generation, can also result in poorer users becoming disadvantaged as NTFP commercialization is intensified. An approach that recognizes such areas of conflict, and attempts to arrive at a realistic balance between development and conservation, is proposed.